Discover EPINER: The innovative project that connects environmental peace and nutrition - Yomayuza, Karoll Valentina (2025)
Colombia's southwestern region known as the 'Macizo Colombiano' is a treasure trove of biodiversity and a source of livelihoods for millions of people. There, an international partnership is joining efforts to strengthen the relationship between environmental conservation and food security. With the support of the Irish Ministry of Foreign Affairs, the Alliance of Bioversity International and CIAT is leading EPINER, a project that promotes environmental peace, nutrition and the reduction of greenhouse gas emissions in the Macizo's communities in Cauca and Putumayo through sustainable agriculture.